IMPLEMENTASI TATA TERTIB SEKOLAH DALAM PENANAMAN BUDAYA DISIPLIN SISWA - Siti Suwaibatul Aslamiyah (TA'LIM : Jurnal Studi Pendidikan Islam, 2020)
Rules are binding ones and become guidelines for schools tocreate a safe and orderly school atmosphere. They are also used as a reference for norm that must be created and implemented by schools, especially in producing good-behaved student. School rules must be implemented properly along with sanctions or penalties for violatorsof discipline in order to facilitate the cultivation of student’s culture of discipline. The support and cooperation of school members could also help create a culture or discipline for students. On account of school discipline rules, student are able to control their disciplinary behavior maximally. In order to achieve the expected disciplinary result, discipline must be carried out effectively. In addition, it is necessary to have the support and cooperation of all school members in order to realize student’s discipline. Therefore, in this paper, the writer will explain about the implementation of school rules in cultivating student’s culture of discipline, obstacles in implementing school rules and how to overcome them, and the role of school members in cultivating student’s culture of discipline. implementation